2000
DOI: 10.1046/j.1365-2664.2000.00481.x
|View full text |Cite
|
Sign up to set email alerts
|

Testing genetically engineered potato, producing the lectins GNA and Con A, on non‐target soil organisms and processes

Abstract: Summary1. Two lectins, concanavalin A (Con A) and Galanthus nivalis agglutinin (GNA), have anti-feedant properties that suggest a potential for the control of invertebrate pests of plants. We tested potato plants genetically engineered to produce each of these lectins constitutively, as well as the puri®ed lectins, for possible non-target eects.2. Laboratory studies with soil bacterial communities and a ciliate protozoan could detect no direct eect of either lectin over a range of concentrations. There was a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
41
0
2

Year Published

2001
2001
2011
2011

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(47 citation statements)
references
References 33 publications
4
41
0
2
Order By: Relevance
“…Previous studies in which microbial communities were examined throughout a field season have often indicated that there is seasonal variability (7,16,17,19,25,26,34). The results of the present study also show that microbial community structure was influenced by seasonal variation, as indicated by significant changes in the CLPP and fatty acid composition of the microbial community associated with the time of sampling.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Previous studies in which microbial communities were examined throughout a field season have often indicated that there is seasonal variability (7,16,17,19,25,26,34). The results of the present study also show that microbial community structure was influenced by seasonal variation, as indicated by significant changes in the CLPP and fatty acid composition of the microbial community associated with the time of sampling.…”
Section: Discussionsupporting
confidence: 70%
“…Denaturing gradient gel electrophoresis analysis of the bacterial rhizosphere community associated with the transgenic potatoes revealed seasonal shifts in the composition of the microbial community (26). Furthermore, the communitylevel physiological profiles (CLPP) of the microbial community associated with another transgenic potato that produced Galanthus nivalis agglutinin and concanavalin A lectins were also subject to seasonal variation (17).…”
mentioning
confidence: 99%
“…Several previous studies describing the effects of GMOs on the structure of microbial communities have shown that the effect is temporary and depends on the presence or absence of transgenic plants. For example, seasonal variation in the microbial community structure associated with GM plants has been shown, with no persistence into the next field season, at least according to studies on GM canola and potato (17,27). Variable differences in the microbial communities between GM and WT poplars were observed in the present study, which were dependent on the stages of poplar growth, and did not continue into the late growth stage.…”
Section: Discussionmentioning
confidence: 49%
“…In fact, many studies showed that soil microbes represent important key nontarget organisms able to highlight unforeseen collateral effects of transgenic plants on natural and agricultural ecosystems. For example, GM potato lines producing Galanthus nivalis agglutinin and Brassica napus resistant to the herbicide glyphosate modified the composition and diversity of soil and rhizospheric microbial communities (22,63). Other works reported different effects of GM plants on soil microorganisms, mainly at the rhizosphere level, where root exudates directly affect the composition of microbial soil communities, in terms of both structure and function (5,21,37,38,50,60,61,64,66,80).…”
mentioning
confidence: 99%